Body, performance and struggle: Towards an aesthetics of moral recognition - Bazzurro Gambi, Leonello (Resonancias. Revista de Filosofía, 2016)
The Intersubjective Recognition (Anerkennung) is a fundamental principle for some branch of contemporary critical theory (A. Honneth, N. Fraser, Ch. Taylor, J. Butler, etc.). Mostly studied in social, cultural and moral terms, the dimension of aesthetics has been neglected. The present paper attempts to address the aesthetic potential of the recognition in terms of “inter-body” (Merleau-Ponty) performance and, at the same time, it is analized, particularly, the use that recognition has in Dos amerindios no descubiertos, a latinamerican performance by Coco Fusco and Gómez Peña.